Phytohaemagglutinin (PHA) induced lymphocyte transformation and toxoplasma gondii antibody studies in primary biliary cirrhosis. Evidence of impaired cell-mediated immunity - Macsween, R. N. M. (1973)
Phytohaemagglutinin (PHA) induced dose-response lymphocyte transformation has been studied in a group of patients with primary biliary cirrhosis. There is a marked reduction in responsiveness, particularly with low doses of PHA. These observations, together with the finding of a raised incidence (7%) of high titre Toxoplasma gondii antibody in primary biliary cirrhosis patients, are adduced as evidence of impaired cell-mediated immunity in this disease.